36.6k views
5 votes
Help in multiplying binomials 1.) (X-7)^2 —> (x • x) (-7 • -7)2.) (3x-4)^2 —> (3x • 3x) (-4 • -4)

User Tipsy
by
5.0k points

1 Answer

4 votes

Given the expressions:


\left(X-7\right)^2
\mathrm{Apply\:Perfect\:Square\:Formula}:\quad \left(a-b\right)^2=a^2-2ab+b^2

Using FOIL:


\left(X-7\right)^2=X^2-2X\cdot\:7+7^2=X^2-14X+49

Similarly, given the expression provided, we obtain:


\left(3x-4\right)^2=\left(3x\right)^2-2\cdot\:3x\cdot\:4+4^2=\quad9x^2-24x+16

User Pankaj Gupta
by
5.7k points